A seven-year study on the effect of the pre-erythrocytic malaria vaccine candidate RTS,S/AS01 (E) on blood stage immunity in young Kenyan children - Ndungu, Francis M. (Wellcome Open Res, 2019)
Background: RTS,S/AS01 (E), the most advanced malaria vaccine confers partial immunity. The vaccine-induced pre-erythrocytic immunity reduces exposure to blood-stage parasites, delaying acquisition of antibodies to blood-stage antigens.  However, the duration of this effect is unknown. Methods: We measured, by enzyme-linked immunosorbent assay, IgG-antibodies to 4 Plasmodium falciparum blood-stage antigens (AMA1, MSP1 (42), EBA175, and MSP3) on 314 children randomized to receive RTS,S/AS01 (E) or Rabies vaccine at 5 – 17 months of age in a phase 2b trial in Kenya, and thereafter participated in a 7-year study of the duration of vaccine immunity. Results: Antibody levels to MSP1 (42), AMA1 and EBA175 were slightly lower among the RTS,S/AS01 (E) recipients, relative to the Rabies-control vaccinees, during the first 48 months of surveillance. Irrespective of vaccine arm, antibody levels to merozoite antigens were positively associated with the risk for malaria. However, this was only apparent at high levels for EBA175 and AMA1 and was not evident after adjusting for heterogeneity in malaria-exposure. Among children with asymptomatic parasitaemia, antibody levels were associated with reduced clinical malaria. Conclusions: The reduction in levels of antibodies to blood-stage antigens induced by vaccination with RTS,S/AS01 (E) can last for several years. In absence of asymptomatic infection, anti-merozoite antibody levels were unreliable correlates of clinical immunity.